Wireless SAW-based temperature sensor - Ying, Charlton Zheng. (2010)
A 440MHz wireless SAW-based temperature sensor has been proposed on a 41o YX LiNbO3 piezoelectric substrate. Reflective delay line composed of an interdigital transducer (IDT) and several reflectors was used as the sensor element. A high frequency of 440MHz allowed a compact antenna to be designed and integrated unto one device. Interdigital transducers (IDT) patterns and different reflector configurations were studied and proposed in this project. Three types of IDT, mainly basic single electrode IDT, split finger electrode IDT and floating electrode unidirectional IDT were chosen. The shorted circuit grating reflector was chosen for the reflector configuration. Three objectives were to be met based on different reflective delay line designs; verification of accuracy and precision increase with increasing number of reflectors, maximize utilization of energy from a bidirectional IDT and lastly, overcome effect of multiple reflections with a dual track SAW device. In total, eight different SAW device designs were proposed and each design was repeated five times when designing a photolithographic mask to ensure fair comparison and conclusion upon characterization. Various different antenna configurations were considered as well. As the antenna would be integrated unto a single device, it is important to consider an antenna that does not require grounding. An antenna electrode pad photolithographic was also fabricated. Fabrication of the SAW device was carried in a two step process with the first being patterning of the IDT using image reversal, lift-off processing, followed by patterning of the antenna electrode pad with a similar lift-off process. However, the photoresist development was poor and positive lithography process and selective etching was considered next.